Physical Protection System, Corrective Actions, and Weaknesses Identification Based on Nuclear Security Series: The Hypothetical Atomic Research Institute (HARI) Case - Ouadie Kabach (International Journal of Nuclear Security, 2020)
The paper is an attempt, based on the IAEA’s Nuclear Security Series (NSS), to identify any unacceptable dysfunction of Physical Protection System (PPS) of the Material Test Reactor (MTR) facility in a Hypothetical Atomic Research Institute (HARI). The evaluation of an existing or a proposed PPS requires a methodical approach whereby the ability of the security system to meet defined protection goals as the safeguard against possibility of sabotage and theft should be measured. Without such kind of careful assessment, the PPS might waste valuable resources on unnecessary protection or, worse yet, fail to provide adequate protection at critical points of the facility. In this work, an assessment of the PPS weaknesses for a hypothetical facility against malicious acts is presented. Hence, those weaknesses are founded during the examination of the site to build a 3D computerized simulation to simulate force engagement to evaluate the physical protection system effectiveness. Based on the IAEA nuclear security series publications, the paper proposes a new layout to correct the vulnerabilities, and another analysis of the changes made for the MTR wall thicknesses access control and the redesigned building plan.
Keywords: Nuclear Security Series; Physical Protection System; Hypothetical Atomic Research Institute; effectiveness.